O perfil de liderança e o seu impacto sobre uma equipe de médicos obstetras de um hospital terciário da região metropolitana de Porto Alegre - Barth, Mariana Barth de (Universidade do Vale do Rio dos Sinos, 2016)
The impact of different leaders along with major teams is subject of extreme notability today, since companies have to constantly deal with change and adversity in search of performances and results. This article aims to analyze the profile of leadership and the impact on a team of obstetricians of a tertiary hospital in the metropolitan area of Porto Alegre, as well as to characterize the profile of leaders who have worked in the hospital (obstetrics division) in the past 5 years. It also targets the perception of the group of obstetricians led, as well as their perception to the team's performance during the administration of different head physicians. Finally, this study is intended to indicate the skills necessary for an effective leader the team. For collected data was carried out a questionnaire among obstetricians who work in this hospital. The approach is qualitative with content analysis. The results of this study indicate that the competence of leadership when worked in various aspects, can take the organization to the achievement of positive results.
Keywords: Liderança; Gestão de pessoas; Desenvolvimento de competências; Leadership; People management; Competences development